Analysis of Gender Gaps in Economic Decision-Making: The Impact of MSMEs Empowerment on the Gender Development Index - Muphimin (CV. Get Press Indonesia, 2026)
Gender-based disparities in economic decision-making remain a systemic obstacle to inclusive growth within emerging economies. This study evaluates the impact of Micro, Small, and Medium Enterprise (MSMEs) empowerment on the Gender Development Index (GDI) in Indonesia, hypothesizing that financial autonomy exerts a more profound influence than mere participation volume. Utilizing a quantitative secondary data analysis design, the research examines a population of 64.5 million MSMEs units across 38 Indonesian provinces from 2023 to 2024. Multiple linear regression was employed to analyze the influence of female-led business ratios and credit accessibility indices as independent variables against GDI scores. The findings reveal a significant positive correlation, where credit access demonstrates a more dominant impact compared to the sheer quantity of business units. In conclusion, fundamentally elevating the GDI necessitates a reform of credit-scoring systems and institutional support for the care economy to liberate women's productive time.